An interactive whiteboard student survey: Development, validity and reliability - Turel, Yalin Kilic (Pergamon-Elsevier Science Ltd, 2011)
The interactive whiteboard (IWB) has become a popular technology for instructors over the last decade. Though research asserts that the IWBs facilitate learning in different ways, there is a lack of studies examining actual IWB use in classroom settings based on learners' perspectives by means of valid instruments. The purpose of this study is to develop a valid and reliable interactive whiteboard student survey in order to evaluate the IWB use based on perceptions of students who have been taught with IWBs. In establishing the theoretical base of the survey, the Technology Acceptance Model (TAM) and constructivist learning theories were considered. In addition, with respect to IWB use in classrooms, a number of studies emanated from countries such as the UK, the USA, and Australia were examined, and similar research questionnaires and findings and also reflections of students about IWBs were utilized to create an item pool. A 39-item survey was conducted among middle school students (N = 263) from the city of Istanbul in Turkey. Collected data was exposed to exploratory factor analysis and resulted in a 26-item, three-factor survey, whose factors were named as the perceived efficiency of IWB, perceived learning contribution and motivation, and the perceived negative effects of IWB. The results of the analyses illustrated that this new IWB student scale, which explains 50% of the total variance with a good level of Cronbach's Alpha coefficient (0.93) is a valid and reliable instrument designed specifically for measuring the use of IWBs in real classroom settings. Besides, theoretical foundations of interactive whiteboard use, the development process of the instrument, and results of validity and reliability analyses were discussed in detail. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Elementary education; Evaluation methodologies; Improving classroom teaching; Interactive learning environments; Teaching/learning strategies; Interactive whiteboard